Conference review: Symposium 25: Reconstructing Ideas and Actions - Mariana Sacchi (EXARC Journal)
17th Argentina’s National Archaeological Congress. Symposium 25: Reconstructing ideas and actions: Actualistic Studies and Experimental Approaches to Archaeology. For many years, actualistic studies have been used largely as a bridging link between archaeological data describing how people use objects with the human behaviours or natural processes associated with this use. This development of Middle Range Theory has many fields of application.